Cognizance Amongphysiotherapy Clinicians and Students in Pelvic Girdle Dysfunction- Qualitative Analysis - S.F.Mariyam Farzana1 , M.S.PawanKumar2 , D.Malarvizhi3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Low back pain of pelvic girdle dysfunction origin is most prevalent among all age group,hence there isconstant need of updates in diagnosis and therapeutic approaches,manual physiotherapy gained an adequateimportance in addressing pelvic girdle dysfunctions,with an objective of understanding the awareness ofpelvic girdle dysfunctions among the clinicians and students, a self-administered questionnaire was designedand administered in pre-conference workshop pelvic girdle dysfunction dogmas in diagnosis and approachat SRM college of physiotherapy SRM Institute of Science and technology Chennai India,based on theresponse and through the statistical analysis it was found that the awareness was lacking and there was alsoneed to focus on the clinicians and student community towards pelvic girdle dysfunctions and its basics,this may be beneficial in enhancing better patient care services and evidence in framing up clinical practice.